National Minority Education in Croatia - Mesić, Milan; Baranović, Branka (2005)
the article treats national minority rights in Croatia, especially in the sphere of education. It presents different models of schooling depending of the size of particular minorities, as well as coverage of minority pupils by each of them.
Nedostaje podatak o stranicama. (admin.)
Projekt MZOS
ENG